Probing PARP1-inhibitor complexes for the development of novel inhibitors - Saqib, U.; Baig, M. S. (Cellular and Molecular Biology, 2014)
Poly (ADP-ribose) polymerase 1 (PARP1) is the most important member of the PARP family which has been shown to have a direct involvement in the development of cancer. A strategy to rationalize the structure based drug discovery of PARP1 inhibitors has been discussed. So far studies regarding varied scaffold PARP1 inhibitors have been done, however the current study focus on how the available data from potent PARP1 inhibitors could be combined and utilized for developing a robust model for the development of novel inhibitors. Through detailed analyses of PARP1-inhibitor binding, a pharmacophore model has been developed followed by a virtual screen of potential inhibitors. The resulting high-affinity binding hits following the defined pharmacophore model and making the critical interactions were selected as final potential leads. Hence, using the approaches of pharmacophore design, docking based virtual screening and conformation alignment, we have identified important leads which satisfy all parameters of the screening process. The developed pharmacophore model as well as the strategy is very straightforward for screening novel inhibitors and could thus be used as a prototype for PARP1 structure based drug discovery.